NOTIONS OF ADDICTION IN THE TIME OF THE FIRST OPIUM WAR*. (29th October 2015) - Unknown
Abstract: This article explores whether the British decision-makers and public were conscious of the habit-forming nature of opium at the time of the Chinese war of 1839–42, the First Opium War. While most political historians have assumed that the British authorities understood the nature of the drug, social historians argue that notions of addiction only arose, in Britain, at the end of the nineteenth century. Examining the abundant press, pamphlet, and parliamentary literature generated by the war debate, this article examines in what terms opium use was characterized. It considers the groups that intervened on both sides of the debate and draws lessons from the arguments they deployed for and against the war. Situating the source literature within the context of early Victorian values and mores, finally, it argues that the British leaders and political nation were aware of the drug's habit-forming properties. Not only was it widely recognized that it was something dangerous that was being introduced, at the point of a gun, into China, but there can be said to have existed, in Britain, a layman's notion of drug addiction.